Water-soluble unit dose articles

CN122917867APending Publication Date: 2026-10-16PROCTER & GAMBLE CO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610391377.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-01
Filing Date
2026-03-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

这种限制可影响它们的处置、运输和应用,使它们不太适合需要稳健包装解决方案的产品

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present disclosure provides a water-soluble unit dose article made from a water-soluble film, wherein the water-soluble film comprises a water-soluble polymer, the water-soluble polymer comprising a blend of: i) an alginate; and ii) a caseinate polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] A water-soluble unit-dosage article made from a water-soluble film comprising a water-soluble polymer, wherein the water-soluble polymer comprises a blend of the following substances:

[0002] i) Alginate; and

[0003] ii) Caseinate polymers. Background Technology

[0004] The development of water-soluble membranes has garnered significant attention across various industries, including packaging, pharmaceuticals, and household products. These membranes offer a convenient way to deliver dosages of active ingredients while reducing the environmental impact associated with traditional packaging materials.

[0005] Traditional water-soluble membranes often face compatibility issues with various detergent compositions, especially liquid detergent compositions. Many commercially available detergents contain surfactants, organic solvents, and other chemical agents that can interact adversely with synthetic membranes, such as causing overplasticization, leading to membrane degradation or overall damage. This incompatibility can result in premature dissolution, loss of function, and shortened shelf life.

[0006] While some existing water-soluble membranes exhibit good solubility and dissolution rate, they often lack mechanical strength and durability. This limitation can affect their handling, transportation, and application, making them less suitable for products requiring robust packaging solutions. During the manufacture of detergent sachets, the membrane must be manipulated and sealed. High elongation at break allows the membrane to withstand mechanical stress during manufacturing without compromising its integrity.

[0007] In the field of water-soluble membranes, polyvinyl alcohol (PVA) has been widely used due to its advantageous properties, including good film-forming ability, water solubility, and mechanical strength. However, while PVA-based membranes have been successful in various applications, there is still a desire to find alternative membranes made from natural materials that exhibit good compatibility with detergent compositions and good mechanical strength and durability. Summary of the Invention

[0008] A first aspect of the present invention is a water-soluble membrane comprising a water-soluble polymer comprising a blend of alginate and caseinate polymers.

[0009] Surprisingly, the membranes according to the invention exhibit good compatibility with detergent compositions, especially liquid detergent compositions, and good mechanical properties, superior to alginate membranes or caseinate polymer membranes.

[0010] This invention relates to a water-soluble unit-dosage article comprising a water-soluble membrane. The water-soluble membrane comprises a water-soluble polymer, wherein the water-soluble polymer comprises a blend of alginate and caseinate polymers. Surprisingly, the membrane according to the invention exhibits good compatibility with detergent compositions, particularly liquid detergent compositions, and good mechanical properties superior to alginate membranes or caseinate polymer membranes. The water-soluble unit-dosage article according to the invention comprises a treatment composition and at least one internal compartment, wherein the treatment composition is contained within the at least one compartment. The treatment composition is selected from laundry detergent compositions, fabric softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof. Detailed Implementation

[0011] Water-soluble membrane

[0012] The water-soluble membrane comprises a water-soluble polymer, wherein the water-soluble polymer comprises a blend of alginate and caseinate polymers. The alginate and caseinate polymers are described in more detail below.

[0013] The water-soluble membrane of the present invention is soluble in water. The water-soluble membrane preferably has a thickness between 30µm and 150µm, more preferably between 50µm and 100µm, and most preferably between 60µm and 85µm.

[0014] Water-soluble membrane properties :

[0015] As described in column 8, lines 10 through 57 of U.S. Patent No. 7,022,656, according to MonoSol Test Method 205 (MSTM 205), the dissolution time of the water-soluble membrane at 10°C with a thickness of approximately 76 micrometers is preferably less than 90 seconds, preferably less than 60 seconds, and more preferably less than 30 seconds. Preferably, according to MonoSol Test Method 205 (MSTM 205), the dissolution time of the water-soluble membrane at 5°C with a thickness of approximately 76 micrometers is less than 300 seconds, preferably less than 200 seconds, and more preferably less than 180 seconds. Preferably, according to MonoSol Test Method 205 (MSTM 205), the disintegration time of the membrane at 10°C with a thickness of approximately 76 micrometers is approximately 40 seconds or less, or approximately 30 seconds or less. Even more preferably, according to MonoSol test method 205 (MSTM 205), the disintegration time of the membrane at a temperature of 5°C and a thickness of about 76 micrometers is about 120 seconds or less, or about 80 seconds or less.

[0016] The membrane disintegration time (I) and membrane dissolution time (S) can be corrected to the standard or reference membrane thickness (76 micrometers) using the exponential algorithms shown in Equations 1 and 2 below, respectively.

[0017] I-calibration = I-measurement × (reference thickness) 2 / Measuring thickness 2 )

[0018] S-correction = S-measurement × (reference thickness) 2 / Measuring thickness 2 )

[0019] Generally, higher tensile strength values ​​are desirable because they will produce stronger water-soluble unit-dose articles. Higher e-modulus values ​​are desirable from the perspective of providing water-soluble unit-dose articles with greater stiffness and a lower likelihood of deformation and adhesion when loaded on top of each other during production. Preferably, when measured at 23°C and 40% RH, the water-soluble film has a tensile strength or stress at break of at least 20 N / mm², preferably between 20 N / mm² and 80 N / mm², more preferably between 25 N / mm² and 80 N / mm², a modulus at at least about 20 N / mm² at 10% elongation, and a stress at at least 12 N / mm² at 100% elongation. Further, the water-soluble film has a tensile strain at break of about 25% to about 1600%, preferably 50% to 1200%, more preferably about 75% to about 800%, as measured by the same method. When measured at 100°C and 40%RH, the water-soluble membrane exhibits at least approximately 50% of the tensile strain at break, as measured using the same method.

[0020] Preferably, according to OECD 301B testing, the water-soluble membrane and / or water-soluble polymer resin and / or water-soluble polymer alone have a biodegradation rate of at least 60%, preferably at least 65%, more preferably at least 70%, or at least 60%, preferably at least 65%, more preferably at least 70% after 60 days, or after 28 days.

[0021] Preferably, the water-soluble film has a glass transition temperature of less than -5°C and a melt transition temperature of greater than 80°C, as measured by the DSC standard procedure.

[0022] The water-soluble film can be further plasticized upon contact with the liquid detergent composition, resulting in swelling of the water-soluble film (positive film swelling value). Alternatively, the water-soluble film can also be deplasticized upon contact with the liquid detergent composition, resulting in deswelling of the water-soluble film. A negative film swelling value can result in a brittle film upon product aging, while a film swelling value greater than 15% can cause the entire unit dose of the article to become soft upon aging and is therefore aesthetically unappealing. Preferably, the film swelling value is between -15% and 15%, more preferably between 0% and 15%, or between 5% and 15%.

[0023] Preferably, the weight ratio of alginate to caseinate polymer is 90:10 to 10:90, and more preferably 75:25 to 25:75.

[0024] The water-soluble polymer may be between 50% and 95% by weight of the membrane, preferably between 55% and 90%, and more preferably between 60% and 80%.

[0025] Preferably, the water-soluble film contains a non-aqueous plasticizer. Preferably, the non-aqueous plasticizer is selected from polyols, sugar alcohols, and mixtures thereof. Suitable polyols include those selected from the group consisting of: glycerol, diglycerol, ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, up to 400 MW of polyethylene glycol, neopentyl glycol, 1,2-propanediol, 1,3-propanediol, dipropylene glycol, polypropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, and polyether polyols, or mixtures thereof. Suitable sugar alcohols include those selected from the group consisting of: isomaltitol, maltitol, sorbitol, xylitol, erythritol, ribitol, galactitol, pentaerythritol, and mannitol, or mixtures thereof. More preferably, the non-aqueous plasticizer is selected from glycerol, 1,2-propanediol, dipropylene glycol, 2-methyl-1,3-propanediol, trimethylolpropane, triethylene glycol, polyethylene glycol, sorbitol, or mixtures thereof, most preferably from glycerol, sorbitol, trimethylolpropane, dipropylene glycol, and mixtures thereof. A particularly suitable plasticizer system comprises a blend of glycerol, sorbitol, and 2-ethyl-2-hydroxymethyl-1,3-propanediol. Another particularly suitable plasticizer system comprises a blend of glycerol, dipropylene glycol, and sorbitol. Preferably, the film contains between 5% and 50% by weight of the film, preferably between 10% and 40%, more preferably between 20% and 30% of a non-aqueous plasticizer.

[0026] Preferably, the water-soluble film according to the invention comprises a surfactant. Preferably, the water-soluble film comprises a surfactant in an amount between 0.1% and 5% by weight of the water-soluble film, preferably between 1% and 3%. Suitable surfactants may include nonionic, cationic, anionic, amphoteric, and zwitterionic categories. Suitable surfactants include, but are not limited to, polyoxyethyleneized polypropylene glycol, alcohol ethoxylates, alkylphenol ethoxylates, tertiary acetylenols and alkanolamides (nonionic), polyoxyethyleneized amines, quaternary ammonium salts and polyoxyethyleneized quaternary ammoniums (cationic), and amine oxides, N-alkyl betaine and sulfobetaine (zwitterionic). Other suitable surfactants include sodium sulfosuccinate, acylated fatty acid esters of glycerol and propylene glycol, lactams of fatty acids, sodium alkyl sulfate, polysorbate 20, polysorbate 60, polysorbate 65, polysorbate 80, lecithin, acetylated fatty acid esters of glycerol and propylene glycol, acetylated fatty acid esters, and combinations thereof.

[0027] Preferably, the water-soluble membrane according to the invention comprises a lubricant / stripping agent. Suitable lubricants / stripping agents may include, but are not limited to, fatty acids and their salts, fatty alcohols, fatty acid esters, fatty amines, fatty amine acetates, and fatty amides. Preferred lubricants / stripping agents are fatty acids, fatty acid salts, and fatty amine acetates. The amount of lubricant / stripping agent in the water-soluble membrane is in the range of 0.02% to 1.5%, preferably 0.1% to 1%, based on the weight of the water-soluble membrane.

[0028] Preferably, the water-soluble film comprises fillers, expanders, anti-blocking agents, anti-sticking agents, or mixtures thereof. Suitable fillers, expanders, anti-blocking agents, anti-sticking agents, or mixtures thereof include, but are not limited to, starch, modified starch, cross-linked polyvinylpyrrolidone, cross-linked cellulose, microcrystalline cellulose, silica, metal oxides, calcium carbonate, talc, and mica. Preferred materials are starch, modified starch, and silica. Preferably, the amount of fillers, expanders, anti-blocking agents, anti-sticking agents, or mixtures thereof in the water-soluble film is in the range of 0.1% to 25% by weight of the water-soluble film, preferably 1% to 10%, more preferably 2% to 8%, and most preferably 3% to 5%. In the absence of starch, a preferred range for suitable fillers, expanders, anti-blocking agents, anti-sticking agents, or mixtures thereof is 0.1% to 1% by weight of the water-soluble film, preferably 4%, more preferably 6%, even more preferably 1% to 4%, and most preferably 1% to 2.5%.

[0029] Preferably, as measured by Karl Fischer titration, the residual moisture content of the water-soluble membrane according to the invention is at least 4% by weight of the water-soluble membrane, more preferably in the range of 4% to 15%, and even more preferably 5% to 10%. The membrane has been pre-conditioned for 24 hours at 20°C and 60% relative humidity before the residual moisture content is determined.

[0030] Preferably, the water-soluble membrane according to the invention contains an aversive agent, more preferably a bittering agent. Suitable bittering agents include, but are not limited to, naringin, sucrose octaacetate, quinine hydrochloride, benzyl dinatamide, or mixtures thereof. Any suitable amount of the aversive agent may be used in the membrane. For water-soluble membranes, suitable levels include, but are not limited to, 1 ppm to 5000 ppm, or even 100 ppm to 2500 ppm, or even 250 ppm to 2000 rpm.

[0031] The water-soluble film according to the invention can be opaque, transparent, or translucent. The water-soluble film according to the invention may include a printing area. The printing area can be implemented using standard techniques such as flexographic printing or inkjet printing.

[0032] The water-soluble film or water-soluble unit-dose product, or both, according to the invention can be coated with a lubricant. Preferably, the lubricant is selected from talc, zinc oxide, silicon dioxide, siloxane, zeolite, silicic acid, alumina, sodium sulfate, potassium sulfate, calcium carbonate, magnesium carbonate, sodium citrate, sodium tripolyphosphate, potassium citrate, potassium tripolyphosphate, calcium stearate, zinc stearate, magnesium stearate, starch, modified starch, clay, kaolin, gypsum, cyclodextrin, or mixtures thereof.

[0033] Alginate

[0034] Alginate is a naturally occurring polysaccharide derived from brown algae (Phaeophyceae), particularly from the cell walls of species such as *Laminaria* and *Ascophyllum*. It consists of two monomeric units: β-D-mannuronic acid (M) and α-L-guluronic acid (G), arranged in different sequences and proportions, resulting in homopolymer blocks (GG or MM) and heteropolymer blocks (MG). Alginate is widely recognized for its unique properties, including gel-forming ability, biocompatibility, and biodegradability, making it an attractive material for a variety of applications, including food, pharmaceuticals, and biodegradable membranes.

[0035] Algates are linear copolymers, and their properties can be influenced by the ratio of M-blocks to G-blocks. The presence of G-blocks contributes to the properties of alginate in the presence of divalent cations (such as calcium ions, Ca2+). 2 The ability to form a gel due to ionic crosslinking in the presence of ⁺).

[0036] Alginate is soluble in water, particularly under alkaline conditions, where it forms a viscous solution. This solubility is crucial for its application in water-soluble membranes, as it allows for easy processing and film formation.

[0037] A key feature of alginate is its ability to gel upon the addition of calcium ions or other divalent cations. This gelation mechanism can be used to create films exhibiting controlled-release properties, suitable for encapsulating active ingredients or detergents.

[0038] Alginate is biodegradable, breaking down into non-toxic byproducts, which aligns with the growing demand for sustainable materials.

[0039] The synergistic effect between alginate and caseinate polymers improved the overall performance of the water-soluble film, resolved the compatibility issue with detergent compositions, and

[0040] It also exhibits enhanced mechanical strength, especially elongation properties.

[0041] Caseinate polymers

[0042] Casein is a milk-derived protein that is relatively insoluble in water. It is typically obtained by precipitation after adding acid (casein acid) or rennet (enzyme chymotrypsin). Casein salts are defined as salts of casein; their counterions are typically selected from the group consisting of calcium, potassium, ammonium, magnesium, and sodium, or mixtures thereof, with sodium being the most preferred.

[0043] The water-soluble membrane according to the invention comprises a water-soluble polymer comprising a blend of a caseinate polymer and an alginate, wherein the caseinate polymer is preferably selected from an alkali metal salt of caseinate, more preferably sodium caseinate.

[0044] Although it is stated that the polymer according to the invention comprises caseinate, in practice, the caseinate will be a mixture of caseinate and casein impurities. The relative weight ratio of casein impurities to caseinate is a function of the pH of the water-soluble membrane. Therefore, when tyrosine salts are referred to herein, this encompasses pure sodium caseinate as well as certain levels of casein impurities.

[0045] Unwilling to be bound by theory, casein is composed of a(s1)-, a(s2)-, β-, and κ-casein. Like any protein, casein is made up of hundreds of individual amino acids, each of which can carry a positive or negative charge, depending on the pH of the surrounding system. At certain pH values, all the positive and negative charges on casein are balanced (i.e., the net charge on the protein is zero); this pH value is known as the isoelectric point (IEP), and the isoelectric point of casein is 4.6. The IEP is the pH at which proteins are least soluble. Therefore, to make casein soluble, it is used in the form of casein salts, as alkaline conditions make casein soluble.

[0046] Preferably, the water-soluble polymer is present in 60% to 80% by weight of the water-soluble film according to the invention, and is composed of a mixture of alginate and caseinate polymers.

[0047] Methods of making membranes

[0048] The water-soluble film according to the invention can be formed by blending and co-casting alginate and caseinate polymers of the type and amount described herein with preferred and optional second additives described herein in a casting solution. If the polymers are mixed first, the water-soluble film is preferably formed by casting the resulting mixture (e.g., together with other plasticizers and other additives) to form a film. Another feature is that the water-soluble film is formed by extrusion, such as blow molding. Most preferably, the water-soluble film according to the invention is prepared by solvent casting.

[0049] Water-soluble unit dose products

[0050] This invention relates to a water-soluble unit-dose article comprising the water-soluble membrane described above, a treatment composition, and at least one internal compartment, wherein the treatment composition is contained within the at least one compartment. The treatment composition is described in more detail below.

[0051] The water-soluble unit-dose article includes a water-soluble membrane shaped such that the unit-dose article includes at least one internal compartment surrounded by the water-soluble membrane. The unit-dose article may include a first water-soluble membrane and a second water-soluble membrane sealed to each other to define the internal compartment. The water-soluble unit-dose article is configured such that the treatment composition does not leak out of the compartment during storage. However, when the water-soluble unit-dose article is added to water, the water-soluble membrane dissolves, releasing the contents of the internal compartment into the washing liquid.

[0052] A compartment should be understood as a sealed internal space within a unit dose of the product, which holds the detergent composition. During manufacturing, a first water-soluble film may be formed into an open compartment into which the treatment composition is added. A second water-soluble film is then covered over the first film in an orientation near the opening of the compartment. The first and second films are then sealed together along a sealing region. Sealing may be performed after solvent sealing, heat sealing, or a combination thereof. The preferred sealing solvent is water.

[0053] A unit-dose article may include more than one compartment, or even at least two compartments, or even at least three compartments. The compartments may be arranged in a superimposed orientation, i.e., one positioned on top of another. In this orientation, the unit-dose article will comprise three layers: a top, a middle, and a bottom film. Alternatively, the compartments may be positioned in a side-by-side orientation, i.e., one immediately adjacent to another. The compartments may even be arranged in a "tire and rim" orientation, i.e., the first compartment is positioned close to the second compartment, but the first compartment at least partially encloses the second compartment, but not completely. Alternatively, one compartment may be completely enclosed within another compartment.

[0054] The unit dose article comprises at least two compartments, one of which may be smaller than the other. The unit dose article comprises at least three compartments, two of which may be smaller than the third. The unit dose article comprises at least four compartments, at least three of which may be smaller than the fourth, and preferably the smaller compartments are stacked on top of the larger compartments. The stacked compartments are preferably arranged side-by-side.

[0055] Preferably, the water-soluble unit dose article includes at least two compartments, more preferably at least three compartments, even more preferably at least four compartments, and most preferably wherein the water-soluble unit dose article includes a first compartment and at least a second compartment stacked on the first compartment, more preferably including at least a third compartment oriented in parallel with respect to the second compartment, and the second and third compartments stacked on the first compartment, and even more preferably including at least a fourth compartment oriented in parallel with respect to the second and third compartments, and the second, third, and fourth compartments stacked on the first compartment.

[0056] In a multi-compartment orientation, the detergent composition may be contained in at least one of the compartments. It may be contained, for example, in only one compartment, or in two compartments, or even in three compartments, or even in all available compartments.

[0057] Each compartment may contain the same or different compositions. The different compositions may all be in the same form, or they may be in different forms.

[0058] A water-soluble unit dose product may include at least two internal compartments, wherein a detergent composition is contained in at least one of the compartments, preferably wherein the unit dose product includes at least three compartments, wherein a detergent composition is contained in at least one of the compartments.

[0059] The water-soluble unit dose product according to the present invention may include at least one

[0060] The water-soluble membrane according to the invention. Alternatively, the water-soluble unit-dose article according to the invention may include at least two or even at least three water-soluble membranes according to the invention. Alternatively, the water-soluble unit-dose article according to the invention may include only the water-soluble membrane according to the invention, i.e., excluding any water-soluble membranes outside the scope of the invention. Preferably, the water-soluble single-compartment unit-dose article or the water-soluble multi-compartment unit-dose article forming the plurality of compartments is a side-by-side configuration, wherein the bottom water-soluble membrane and the top water-soluble membrane encapsulating the single compartment are both water-soluble membranes according to the invention. Alternatively, the top water-soluble membrane or the bottom water-soluble membrane is according to the invention. The water-soluble unit-dose article may be formed as compartments having a stacked configuration. In this configuration, each of the top, bottom, and middle water-soluble membranes may be a water-soluble membrane according to the invention. Alternatively, a combination of, for example, only the middle water-soluble membrane, only the top water-soluble membrane, or only the bottom water-soluble membrane, or any of these water-soluble membranes, may be a water-soluble membrane according to the invention, while the remaining water-soluble membranes are outside the scope of the invention. Preferably, all water-soluble films included in the water-soluble unit dose article are water-soluble films according to the invention. These water-soluble films according to the invention may be chemically and physically identical, or alternatively may be chemically and / or physically different. "Different" means that the first water-soluble film is intended to have at least one chemical and / or physical property different from that of the second water-soluble film. This property can be achieved by selecting different polymer resins, which differ, for example, in terms of average individual polymer solution viscosity, average individual polymer hydrolysis degree, the ratio between the first and second water-soluble polymers, or their mixing. "Target average" takes into account standard polymer variations inherent in any manufacturing process. Alternatively, this property can be achieved by changing the relative content of individual components within the water-soluble film, such as polymer resins, relative to plasticizer or water content, or even changing the exact chemical properties of the additives. The "different" property of the initial film is evaluated before deformation, for example, in which differences in water-soluble film content due to deformation operations, exposure to the encapsulated detergent composition leading to exchange of active substances between the film and the detergent composition, and exchange of active substances with the surrounding storage environment are excluded.

[0061] Treatment composition

[0062] The treatment composition may be selected from laundry detergent compositions, laundry softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof, preferably laundry detergent compositions, preferably liquid, powder, or mixtures thereof, preferably liquid compositions.

[0063] The term liquid includes gels, solutions, dispersions, pastes, or mixtures thereof.

[0064] The term "powder" herein refers to a treatment composition that may contain solid particles or may be a single homogeneous solid. Preferably, the powder treatment composition contains particles. This means that the powder treatment composition contains individual solid particles, unlike a solid that is a single homogeneous solid. The particles may be free-flowing or compacted, preferably free-flowing.

[0065] Preferably, the treatment composition is a laundry detergent composition, and most preferably a liquid laundry detergent composition.

[0066] The laundry detergent composition can be used in hand washing operations or in automatic machine washing operations, preferably in automatic machine washing operations.

[0067] Preferably, the treatment composition comprises a non-soap surfactant, wherein the non-soap surfactant includes anionic non-soap surfactants and nonionic surfactants. Preferably, the treatment composition comprises between 10% and 60% by weight of the treatment composition, more preferably between 20% and 55% of the non-soap surfactant.

[0068] The weight ratio of non-soap anionic surfactant to nonionic surfactant can be 1:1 to 20:1, preferably 1.25:1 to 17.5:1, 1.5:1 to 15:1, or 1.75:1 to 13:1, or 2:1 to 10:1.

[0069] Preferably, the non-soap anionic surfactant comprises linear alkylbenzene sulfonates, alkyl sulfates, or mixtures thereof. The weight ratio of the linear alkylbenzene sulfonate to the alkyl sulfate is 1:2 to 9:1, preferably 1:1 to 7:1, more preferably 1:1 to 5:1, and most preferably 1:1 to 4:1.

[0070] An example linear alkylbenzene sulfonate is C 10 -C 16 Alkylbenzenesulfonic acid, or C 11 -C 14 Alkylbenzene sulfonic acids. The term "straight-chain" in this document refers to alkyl groups that are straight-chain. Alkylbenzene sulfonates are well known in the art.

[0071] Alkyl sulfate anionic surfactants may comprise alkoxylated alkyl sulfates or non-alkoxylated alkyl sulfates or mixtures thereof. Aloxylated alkyl sulfate anionic surfactants are preferably ethoxylated alkyl sulfate anionic surfactants.

[0072] Alkyl sulfate anionic surfactants may include ethoxylated alkyl sulfate anionic surfactants, preferably having a molar average degree of ethoxylation of 1 to 5, more preferably 1 to 3, and most preferably 2 to 3.

[0073] The alkyl sulfate anionic surfactant may comprise non-ethoxylated alkyl sulfates and ethoxylated alkyl sulfates, wherein the molar average degree of ethoxylation of the alkyl sulfate anionic surfactant is 1 to 5, more preferably 1 to 3, and most preferably 2 to 3.

[0074] The alkyl fraction of anionic alkyl sulfate surfactants may preferably be derived from fatty alcohols, carbonyl synthetic alcohols, Guerbert alcohols, or mixtures thereof.

[0075] Preferably, the treatment composition comprises between 10% and 50% by weight of the treatment composition, more preferably between 15% and 45%, even more preferably between 20% and 40%, and most preferably between 30% and 40%.

[0076] Preferably, the nonionic surfactant is selected from alcohol alkoxylates, carbonyl synthetic alcohol alkoxylates, Gelbert alcohol alkoxylates, alkylphenol alcohol alkoxylates, or mixtures thereof.

[0077] The treatment composition preferably contains between 0.01% and 25% by weight of the treatment composition, more preferably between 1% and 22.5%, more preferably between 5% and 20%, and most preferably between 8% and 20%.

[0078] Preferably, the treatment composition comprises between 0.5% and 20% by weight of the treatment composition, more preferably between 1% and 15%, even more preferably between 1.5% and 10%, and most preferably between 2% and 8%, a soap, preferably a fatty acid salt, more preferably an amine-neutralized fatty acid salt, wherein the amine is preferably an alkanolamine, more preferably selected from monoethanolamine, diethanolamine, triethanolamine or mixtures thereof, and more preferably monoethanolamine.

[0079] Preferably, the treatment composition is a liquid treatment composition; more preferably, the liquid treatment composition contains less than 15%, more preferably less than 13%, even more preferably 1% to 12%, and most preferably 5% to 12% water by weight of the liquid treatment composition.

[0080] Preferably, the treatment composition is a liquid treatment composition comprising a non-aqueous solvent selected from 1,2-propanediol, dipropylene glycol, tripropylene glycol, glycerol, sorbitol, polyethylene glycol, or mixtures thereof. Preferably, the liquid treatment composition comprises between 10% and 40%, more preferably between 15% and 30% by weight of the liquid treatment composition.

[0081] Preferably, the treatment composition contains a fragrance.

[0082] Preferably, the treatment composition comprises auxiliary ingredients selected from the group consisting of: enzyme-based detergents, citrates, bleaching agents, bleaching catalysts, dyes, tinting dyes, brighteners, cleaning polymers including alkoxylated polyamines and polyethyleneimine, detergency polymers, surfactants, solvents, dye transfer inhibitors, chelating agents, encapsulated fragrances, polycarboxylate esters, structural agents, pH adjusters, and mixtures thereof.

[0083] Those skilled in the art will know how to formulate and prepare suitable treatment compositions using known knowledge and techniques. Treatment compositions may contain common detergent ingredients, including surfactants, polymers, bleaching agents, enzymes, fragrances, dyes, structural agents, fillers, water, or mixtures thereof.

[0084] Those skilled in the art will know the known techniques for preparing the water-soluble unit dose product according to the present invention.

[0085] Example

[0086] The mechanical properties (elongation at break %) and treatment composition (laundry detergent composition)-membrane interaction (swelling %) of three bio-based water-soluble membranes were defined according to the test methods described herein. Membrane 1 is based on a water-soluble sodium caseinate polymer. Membrane 2 is based on a water-soluble sodium alginate polymer. Membrane 3 is based on a 50 / 50 blend of sodium caseinate and sodium alginate polymers by weight. The data summarized in Table 1 show improved elongation and treatment composition-membrane interaction behavior when the two types of polymers are blended together. For example, while sodium caseinate membranes cannot be used in the manufacture of water-soluble liquid detergent products due to their dissolution into the detergent composition, and sodium alginate membranes cannot be used in the manufacture of water-soluble liquid detergent products due to their non-deformability, the blended membranes exhibit good detergent composition-membrane compatibility characteristics and deformability to produce unit dose products.

[0087] Table 1: Elongation at break (%) of water-soluble membranes

[0088]

[0089] *The membrane dissolves in the treatment composition and is therefore unmeasurable.

[0090] The membrane was too brittle and broke when the solution was removed, therefore the swelling percentage could not be measured due to the membrane area required for the test.

[0091] Method for preparing water-soluble membranes

[0092] A solution of 100% by weight of active alginate or caseinate polymer, or a 50 / 50 blend by weight, was prepared in softened water containing 27% by weight of glycerol (sodium alginate from VWR, sodium caseinate from Thermoscientific). The solution was mixed at 70°C for at least 4 hours to obtain a homogeneous solution, which was then allowed to stand overnight at room temperature to allow for degassing prior to casting. The solution was poured into a thin layer on a PET casting plate through a film coater with a wet gap in the range of 250 μm to 350 μm, and the thin layer was dried overnight at room temperature and 35% rH. The resulting membrane contained 66% by weight of water-soluble polymer resin, 28% by weight of a glycerol plasticizer system, and 6% water. Individual membrane thicknesses are summarized in Table 2 below.

[0093] Table 2: Film Thickness

[0094]

[0095] The membrane is too fragile, causing it to break when the solution band is removed, making measurement impossible.

[0096] Swelling % test :

[0097] Treatment composition

[0098] The following liquid laundry detergent composition was used to evaluate the membrane swelling percentage:

[0099]

[0100] *Lutensol FP620—ethoxylated polyethyleneimine (PEI600EO20) purchased from BASF.

[0101] **Lutensit Z96 (purchased from BASF, a zwitterionic polyamine-zwitterionic hexamethylenediamine: 100% quaternized and approximately 40% of the polyethoxy (EO24) groups are sulfonated), preferably having the following structure).

[0102]

[0103] Prepare water-soluble membrane samples measuring 11 cm x 12 cm and expose them to the test treatment composition. Each test membrane requires 750 ml of this test liquid treatment composition. Cover the bottom of a clean, inert glass container with a thin layer of liquid and spread the first membrane to be tested onto the liquid; gently push any trapped air bubbles to the side. Spread the liquid layer on top of the first membrane sample, then add the second membrane sample. Repeat this process until five membrane samples have been stacked with the intermediate liquid film layer. Then gently pour the remaining liquid on top of the fifth membrane, ensuring the membrane is completely immersed in the liquid. The membrane should remain wrinkle-free and free of air bubbles. Keep the membrane in contact with the liquid and store it in a sealed container at 50°C for 5 days and at 21°C for 1 night. Use a separate glass receiver for each membrane being tested. Then remove the membrane from the storage container and remove any excess liquid from the membrane. Place a sheet of paper on the membrane, lay the membrane on top of the workbench paper, and then thoroughly dry the membrane with dry paper (e.g., a dry paper towel free of fibers that may stick to the membrane surface). Measure the weight of the membrane before and after the immersion test, and calculate the relative weight increase / weight loss, expressed as change % according to the following formula:

[0104] Change % = (Final weight - Starting weight / Starting weight) * 100. Calculate and report the average of five membrane samples for each test solution.

[0105] Negative film swelling values ​​can result in a brittle film during product aging, while film swelling values ​​greater than 15% can cause a unit dose of the product to become soft during aging, and thus be aesthetically unappealing. Preferably, the film swelling value is between 0% and 15%.

[0106] Elongation at break % test

[0107] The procedure includes determining the elongation at break (%) according to ASTM D882 (“Standard Test Method for Tensile Properties of Thin Plastic Sheeting”) or an equivalent method. Film data are collected using an INSTRON tensile testing apparatus (Model 5544 Tensile Tester or equivalent). Tests are conducted in a standard laboratory environment at 23°C ± 2.0°C and 35% ± 5% relative humidity. At least three test specimens are cut with reliable cutting tools to ensure dimensional stability and reproducibility, and each measurement is performed in the longitudinal direction (MD) (where applicable). Test samples were prepared from a single membrane sheet measuring 12 cm in length (MD) by 17 cm in width, and then cut into individual 1" wide (2.54 cm) samples with a thickness of approximately 98 μm. The samples were then transferred to an INSTRON tensile testing machine for testing. The tensile testing machine, equipped with a 500 N load cell and calibrated, was prepared according to the manufacturer's instructions. The correct clamps and faces were assembled (NSTRON clamps have a model 2702-032 face or equivalent, which has a rubber coating and is 25 mm wide). The samples were mounted in the tensile testing machine and analyzed to determine the elongation at break (%). The actual thickness of the water-soluble membrane sample was measured prior to testing, and the mechanical test data were normalized from this actual membrane thickness to the 76-micron test membrane to ensure a fair comparison between the test legs.

[0108] The dimensions and values ​​disclosed herein should not be construed as strictly limited to the precise numerical values ​​cited. Rather, unless otherwise specified, each such dimension is intended to represent the stated value and the range surrounding its functional equivalent. For example, a dimension disclosed as “40 mm” is intended to represent “approximately 40 mm”.

Claims

1. A water-soluble unit-dose article comprising a water-soluble membrane, a treatment composition, and at least one internal compartment, wherein the treatment composition is contained within the at least one internal compartment, the treatment composition being selected from laundry detergent compositions, fabric softening compositions, automatic dishwashing compositions, hard surface cleaning compositions, or mixtures thereof, wherein the water-soluble membrane comprises a water-soluble polymer, the water-soluble polymer comprising a blend of the following substances: i) Alginate; and ii) Caseinate polymers, The water-soluble polymer is between 50% and 95% by weight of the membrane, and the weight ratio of the alginate to the caseinate polymer is between 90:10 and 10:

90.

2. The water-soluble unit dose product according to claim 1, wherein the weight ratio of the alginate to the caseinate polymer is 75:25 to 25:

75.

3. The water-soluble unit dose product according to any one of claims 1 or 2, wherein the caseinate polymer is selected from alkali metal salts of caseinate, preferably sodium caseinate.

4. The water-soluble unit dose article according to any one of the preceding claims, wherein the water-soluble polymer comprises between 55% and 90% by weight of the membrane, more preferably between 60% and 80%.

5. The water-soluble unit dose article according to any one of the preceding claims, wherein the film comprises a non-aqueous plasticizer, preferably wherein the non-aqueous plasticizer is selected from polyols, sugar alcohols, and mixtures thereof, more preferably from glycerol, 1,2-propanediol, trimethylolpropane, dipropylene glycol, 2-methyl-1,3-propanediol, 2-ethyl-2-hydroxymethyl-1,3-propanediol, triethylene glycol, polyethylene glycol, sorbitol, or mixtures thereof, most preferably from glycerol, sorbitol, trimethylolpropane, dipropylene glycol, and mixtures thereof, preferably wherein the film comprises between 5% and 50% by weight of the film, preferably between 10% and 40%, more preferably between 20% and 30% of the non-aqueous plasticizer.

6. The water-soluble unit dose article according to any one of the preceding claims, wherein the water-soluble film comprises a surfactant in an amount between 0.1% and 5%, preferably between 1% and 3%, based on the weight of the water-soluble film.

7. The water-soluble unit dose article according to any one of the preceding claims, wherein the membrane has an elongation at break of about 25% to about 1600%, preferably about 50% to about 1200%, more preferably 75% to 800%, as measured by the method described herein.

8. The water-soluble unit dose article according to any one of the preceding claims, wherein the membrane has a tensile strength (maximum breaking stress) of at least 20 MPa.

9. A water-soluble unit-dosage article according to any one of the preceding claims, wherein the membrane has a swelling of -15% to 15%, or 0% to 15%, or 5% to 15% as measured by the methods described herein.

10. The water-soluble unit dose article according to any one of the preceding claims, wherein the water-soluble membrane contains a residual moisture content of at least 4%, more preferably 4% to 15%, and even more preferably 5% to 10% by weight of the membrane, as measured by Karl Fischer titration.

11. The water-soluble unit dose article according to any one of the preceding claims, wherein the water-soluble film has a thickness between 30µm and 150µm, preferably between 50µm and 100µm, and most preferably between 60µm and 85µm.

12. A method for producing a membrane of a water-soluble unit dose article according to any one of the preceding claims, the method comprising the steps of: i) Dissolve the caseinate polymer, alginate, and optional additives in water to form an aqueous solution; as well as ii) Cast the solution obtained in step i) into a film.

13. The water-soluble unit dose article according to any one of claims 1 to 11, wherein the treatment composition is a laundry detergent composition, preferably the treatment composition is a liquid, powder or mixture thereof, preferably a liquid laundry detergent composition.

14. The water-soluble unit dose article according to any one of claims 1 to 11 or 13, wherein the treatment composition comprises a non-soap surfactant, wherein preferably, the non-soap surfactant is selected from anionic non-soap surfactants, nonionic surfactants, and mixtures thereof, wherein preferably, the treatment composition comprises between 10% and 60% by weight of the treatment composition, more preferably between 20% and 55% of the non-soap surfactant.

15. The water-soluble unit dose article according to any one of claims 1 to 11 or 13 to 14, wherein the treated composition comprises less than 15%, preferably less than 13%, more preferably between 1% and 12%, and most preferably 5% to 12% water by weight of the treated composition.

16. The water-soluble unit-dose article according to any one of claims 1 to 11 or 13 to 15, wherein the treated composition comprises between 10% and 40%, preferably between 15% and 30% by weight of the treated composition.

Citation Information

Patent Citations

  • Water-soluble copolymer film packet

    US7022656B2